Room temperature paramagnetism of ZnO:Mn films grown by RF-sputtering - Oliveira, Filipe André (2010)
ZnO:Mn transparent thin films (thickness b1 μm) with the Mn contents ranging from 1.8 to 3.25 at.% were grown by RF magnetron co-sputtering. The films are nanocrystalline, with wurtzite-structure grains of a typical size of 20 nm and with a preferential orientation of the c-axis perpendicular to the surface. According to the Raman spectroscopy data, Mn mostly substitutes Zn in the lattice sites. In spite of these factors, the nanostructure and the Mn(Zn) substitution, that are considered favorable for ferromagnetism in this material, both magnetic resonance and Faraday effect measurements show paramagnetic behavior of the ZnO:Mn films and the absence of ferromagnetic order at room temperature.